Influence of a complex impeller with tip clearance on the internal and external characteristics of a multiphase pump - Yao, Xin; Shi, Guangtai; Wen, Haigang; Huang, Zongliu (Frontiers in Energy Research, 2022)
With the exploitation of deep sea and desert oil fields, multiphase pumps have stepped into public eyes. However, affected by medium properties and operation environment, traditional multiphase pump performance decrement caused problems such as oil recovery cycle growth and costs rise were appearance. To obtain high head and reliability multiphase pump, this paper used optimization method designed out complex impeller. Took external characteristics as optimization index, selected out head lift 17.2 % as the best complex impeller then used the complex impeller and original impeller to simulate when inlet gas volume fraction was 10%. The results shown that short blade reduced the proportion of high-speed areas, suppressed the low-speed areas appeared on suction surface of long blade and significantly inhibited backflow. At relative position 1.5~2.0 the slope of pressurization curve of complex impeller was larger than the original impeller, pressurization performance increased by 16.34kPa, short blades weakened leakage movement and reduced pressure function on long blades. Moreover, short blades improved the gas aggregation situation made gas masses in the inlet channel closer to the suction of long blade surfaces and the size diminished. Promoted gas distribution uniformity and enhanced flow capacity on inlet. The research provides reference for model optimization and performance improvement of multiphase pump performance in the future.